Patologías bucales asociadas a síndrome de down y parálisis cerebral¨ - González Muñoz, Luis David (2017)
The present research work has as main objective to study the main oral pathologies in patients with disabilities, in the ages of 15 to 45 years of age attended in the period February Octuber 2016. 42 patients were the sample of study. The relevance of this research is due to the lack of interest from the dental point of view to the oral care of people with special abilities as certain anomalies occur over time. The prevention of oral diseases is in this group of patients a fundamental strategy due to the problems. It is a real challenge that requires special preparation to provide an acceptable care. In this group of patients, all techniques of desensitization and modulation of behavior due to they respond very well to this type of techniques. These patients with special abilities in the Foundacón Protección and Descanso de Riobamba were observed considering a sample of 42 people. After the analysis 14 corresponded to Down syndrome and 28 to Cerebral Palsy each of the groups with different types of oral pathologies, the most relevant ones were: dental caries, periodontal disease, bruxism, macroglosia, malocclusion, xerostomia. The most affected group was male gender, the major oral health problem maintains the age group comprised between 28 and 35 years of age